Evaluasi Kepatuhan Penggunaan Obat Antidiabetik Oral Pada Pasien Rawat Jalan Diabetes Melitus Tipe 2 Di Rumah Sakit Universitas Sebelas Maret: EVALUATION OF ADHERENCE TO THE USE OF ORAL ANTIDIABETIC DRUGS IN OUTPATIENTS WITH TYPE 2 DIABETES MELLITUS AT THE UNS HOSPITAL - Latipah, Ayu; Murtisiwi, Lusia; Adiningsih, Retnowati (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2022)
Diabetes mellitus is a chronic disease that can cause complications, both microangiopathy and macroangiopathy if not treated properly. The success of diabetes mellitus therapy is influenced by patient compliance in drug use. The purpose of this study was to determine adherence to the use of oral antidiabetic drugs in outpatients with type 2 diabetes mellitus at Sebelas Maret University Hospital. This research is a non-experimental descriptive research. Sampling was done by purposive sampling in accordance with the inclusion criteria and exclusion criteria that have been determined. Compliance data retrieval using the Medication Adherence Report Scale questionnaire in Indonesian which has been tested for validity and reliability by Alfian (2017) which is distributed to patients. Data collection techniques were direct interviews with patients and filling out a questionnaire for patient data and the MARS-5 medication adherence questionnaire. Data analysis was carried out descriptively by describing the patient's characteristics. Analysis of the level of compliance in this study using a total scoring questionnaire MARS-5. This research has obtained a research permit with an ethical feasibility letter No: 788/VI/HREC/2022. Data collection was carried out in June-July 2022. The results showed that from 205 respondents, the level of adherence to the use of oral antidiabetic drugs included a low adherence rate of 50.2% and a high adherence rate of 49.8%.